Gentamicin pharmacokinetics in patients with malignancies. - Bertino, J S (1991)
The pharmacokinetics of gentamicin were investigated in 880 patients with leukemia (24 patients), other malignancies (211 patients), or no malignancies (645 patients) by using data collected by our Clinical Pharmacy Service. A significant difference was seen in the initial calculated creatinine clearance between the patients with leukemia and the other two groups. No differences in gentamicin pharmacokinetics were seen in patients with other malignancies versus those with no malignancies. Patients with leukemia had significantly faster drug clearance compared with those in the other two groups. A poor predictive value was found for total body clearance of gentamicin versus the initial calculated creatinine clearance in all groups. Multiple logistic regression analysis showed that only the initial calculated creatinine clearance differed in the leukemic group compared with those in the other patients. Our data suggest that no pharmacokinetic difference exists for gentamicin in patients with malignancies.